Artificial photosynthesis processes as a means of producing biofuels. Issue 6 (November 2010) - Wendell, David W
The transition to a sustainable and scalable energy system will require the development of new carbon-neutral fuel technologies. Artificial photosynthesis seeks to meet this need by mimicking the biological energy conversion process, producing biofuels from sunlight. While the process of photovoltaic conversion has existed for almost two centuries, the idea of artificially co-opting and engineering the biological process has been a relatively recent advancement brought about by the exposed molecular workings of cellular-based energy conversion and storage. The following report examines the benefits and limitations of the current artificial photosynthesis strategies developed for storing solar energy as biofuel.